High-strength porous ceramsite and preparation method thereof

By using materials such as secondary aluminum ash and electroplating sludge, combined with auxiliary agents such as fly ash and bentonite, and sintering in the rotary kiln, the problems of uneven foaming and insufficient strength in the preparation of ceramic granules are solved, and high The preparation of strength porous ceramic particles improves the quality and application effect of ceramic particles, while reducing production costs and environmental impact.

CN119461919APending Publication Date: 2025-02-18YUYUAN NINGHAI ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411468346.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ceramic preparation methods may face problems such as uneven foaming and poor strength of ceramic particles during the preparation process, which will affect the quality and application effect of ceramic particles.

Method used

Secondary aluminum ash and electroplating sludge are used as the main components, combined with fly ash, bentonite, flux and binder, and dried, granulated and sintered in a rotary kiln to prepare high-strength porous ceramic granules.

Benefits of technology

The high-strength and porous structure of the ceramite are realized, the density and application effect of the ceramite are improved, and energy consumption and pollutant emissions are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005094026410000051
    Figure BDA0005094026410000051
  • Figure BDA0005094026410000061
    Figure BDA0005094026410000061
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to high-strength porous ceramsite and a preparation method thereof. The high-strength porous ceramsite is prepared from the following raw materials in parts by weight: 30 to 50 parts of secondary aluminum ash, 20 to 40 parts of electroplating sludge, 5 to 10 parts of fly ash, 10 to 20 parts of bentonite, 5 to 10 parts of fluxing agent and 5 to 10 parts of binder, the preparation method comprises the following steps: (1) uniformly mixing secondary aluminum ash, electroplating sludge, fly ash and bentonite, spraying water, continuously stirring, adding a fluxing agent and a binder, uniformly stirring, and aging; and (2) feeding the aged material into a rotary kiln through a screw conveyor, drying, granulating, sintering, and finally cooling. The secondary aluminum ash and the electroplating sludge are taken as main components, and are combined with the fly ash, the bentonite and other auxiliaries, so that the porous ceramsite with relatively high strength is finally obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to high-strength porous ceramsite and a preparation method thereof. Background Art

[0002] Solid waste refers to solid and semi-solid waste materials generated by humans in production, consumption, life and other activities, mainly including solid particles, garbage, slag, sludge, discarded products, etc., which can be roughly divided into three categories: industrial waste, agricultural waste and domestic waste. With the acceleration of urbanization, more solid waste is generated, such as secondary aluminum ash, sludge, etc. If these wastes are not handled properly, they will not only occupy a large amount of land resources, but also may have serious impacts on the environment and human health. Therefore, how to effectively utilize these wastes and transform them into valuable resources has become a hot topic in current research.

[0003] In the technology of waste resource utilization, the preparation of ceramsite has attracted much attention due to its unique advantages. Ceramsite is a lightweight aggregate produced by foaming in a rotary kiln. It has a hard outer shell on the surface. This outer shell is ceramic or glazed, which has the function of water-proofing and air-retaining, and gives ceramsite a higher strength. It can be used to replace gravel and pebbles in concrete in the field of building materials. At the same time, the interior of ceramsite is composed of fine honeycomb micropores. These micropores are all closed and are formed by the gas being wrapped in the shell. This is also the main reason why ceramsite is light. As a man-made lightweight aggregate, ceramsite has a wide range of applications in construction, water treatment, gardening and other fields due to its light weight, porosity, high strength and good thermal insulation. In recent years, researchers have been constantly exploring methods to prepare ceramsite from solid waste in order to maximize resource utilization and protect the environment.

[0004] A Chinese patent document (publication number CN116606123A) proposes a method for preparing ceramsite by in-situ foaming of secondary aluminum ash, using grate bottom ash, secondary aluminum ash and fly ash from municipal solid waste incineration as raw materials, and preparing high-strength and lightweight ceramsite by in-situ foaming technology, which can improve the foaming performance and compressive strength of ceramsite to a certain extent, and then further improve the uniformity of ceramsite pores by adding a composite foam stabilizer, and prepare high-strength and light-weight ideal ceramsite. However, the preparation method of ceramsite may face problems such as uneven foaming and unsatisfactory ceramsite strength during the preparation process, which affects the quality and application effect of ceramsite. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength porous ceramsite in view of the above technical problems, which takes secondary aluminum ash and electroplating sludge as main components, combines fly ash, bentonite and other additives, and finally obtains porous ceramsite with higher strength.

[0006] The high-strength porous ceramsite in the technical solution of the present invention comprises the following raw materials in parts by weight: 30 to 50 parts of secondary aluminum ash, 20 to 40 parts of electroplating sludge, 5 to 10 parts of fly ash, 10 to 20 parts of bentonite, 5 to 10 parts of flux and 5 to 10 parts of binder.

[0007] The present invention uses secondary aluminum ash and electroplating sludge as the main components of ceramsite, combines flux to reduce sintering temperature and improve sintering efficiency, adds binder to adjust the viscosity of the mixture, ensures stability during the molding process, improves the molding performance of particles, and cooperates with fly ash and bentonite to jointly improve the density and strength of ceramsite.

[0008] Furthermore, the secondary aluminum ash is composed of the following components in weight percentage: 5-10% SiO2, 5-10% Al2O3, 1-5% Fe2O3, 1-5% CaO, 3-8% MgO, 0.10-0.40% Cu, 0.01-0.06% Ni, 0.05-0.20% Cr, 0.10-0.50% Zn, 0.03-0.08% Pb, and the balance is Al.

[0009] Furthermore, the electroplating sludge is composed of the following components in weight percentage: 1-5% SiO2, 3-8% Al2O3, 8-15% Fe2O3, 20-28% CaO, 5-10% MgO, 0.05-0.20% Cu, 0.10-0.20% Ni, 0.15-0.25% Cr, 0.30-0.80% Zn, 0.01-0.03% Pb, and the balance is water.

[0010] Furthermore, the flux is one or more of potassium carbonate, borax, anhydrous aluminum fluoride, magnesium fluoride, and calcium carbonate, preferably calcium carbonate.

[0011] Furthermore, the binder is one or more of a silicate binder, a phosphate binder, and an aluminate binder.

[0012] The present invention also provides a method for preparing the high-strength porous ceramsite, comprising the following steps:

[0013] (1) After the secondary aluminum ash, electroplating sludge, fly ash and bentonite are mixed evenly, water is sprayed and stirred continuously, and then flux and binder are added, stirred evenly and aged;

[0014] (2) The aged material is sent to a rotary kiln through a screw conveyor for drying, granulation, sintering, and finally cooling.

[0015] The use of rotary kilns for granulation, drying and high-temperature sintering can improve the cleanliness level of expanded clay production, significantly reduce energy consumption, shorten the production process, improve equipment production efficiency and reduce pollutant emissions.

[0016] Furthermore, the aging time in step (1) is 3 days or more, and the raw materials are fully aged after stirring to ensure the uniformity of the raw materials.

[0017] Furthermore, the moisture content of the material obtained by aging in step (1) is 45% to 50% (mass percentage), the raw material has better applicability and the production is more stable.

[0018] Furthermore, in step (2), the sintering temperature is 1100-1300° C., and the sintering time is 30-60 min. If the sintering temperature is too high, it may cause excessive melting, affecting the pore structure and strength of the ceramsite; if the sintering temperature is too low, it may not be completely sintered, resulting in insufficient product strength.

[0019] Furthermore, in step (2), cooling is performed by using a centrifugal fan to suck in cold air to exchange heat with the ceramsite. Such slow cooling can avoid excessive internal stress in the ceramsite, which may lead to cracking or deformation.

[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0021] (1) Using secondary aluminum ash and electroplating sludge as the main components, combined with fly ash, bentonite and other additives, a porous ceramsite with high strength is finally obtained;

[0022] (2) Flux can reduce sintering temperature and improve sintering efficiency;

[0023] (3) The binder can adjust the viscosity of the mixture, ensure stability during the molding process, improve the molding properties of the particles, and work together with fly ash and bentonite to improve the density and strength of ceramsite;

[0024] (4) Using a rotary kiln for granulation, drying and high-temperature sintering can improve the cleanliness level of ceramsite production, significantly reduce energy consumption, shorten the production process, improve equipment production efficiency, and reduce pollutant emissions;

[0025] (5) By adopting a suitable preparation process, the comprehensive performance of expanded clay can be improved efficiently at a lower cost, and the applicability of raw materials is also better. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0027] The electroplating sludge used in the following embodiments and comparative examples is composed of the following components in weight percentage: 1.11% SiO2, 4.66% Al2O3, 10.71% Fe2O3, 23.41% CaO, 8.87% MgO, 0.11% Cu, 0.14% Ni, 0.20% Cr, 0.56% Zn, 0.01% Pb, and the moisture content is 64.9%; the secondary aluminum ash is composed of the following components in weight percentage: 6.79% SiO2, 8.15% Al2O3, 2.07% Fe2O3, 2.07% CaO, 4.81% MgO, 0.11% Cu, 0.02% Ni, 0.08% Cr, 0.25% Zn, 0.07% Pb, and the balance is Al.

[0028] Example 1

[0029] The method for preparing the high-strength porous ceramsite of this embodiment comprises the following steps:

[0030] (1) 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 15 parts of bentonite were mixed evenly, sprayed with water and stirred continuously, and then 6 parts of calcium carbonate and 6 parts of silicate inorganic adhesive were added, stirred evenly and aged for 5 days;

[0031] (2) The aged material (water content 48%) is sent to a rotary kiln through a screw conveyor for drying and granulation, sintered at 1150° C. for 50 min, and finally cooled to room temperature by using a centrifugal fan to inhale cold air for heat exchange with the ceramsite.

[0032] Example 2

[0033] The method for preparing the high-strength porous ceramsite of this embodiment comprises the following steps:

[0034] (1) 45 parts of secondary aluminum ash, 30 parts of electroplating sludge, 8 parts of fly ash and 12 parts of bentonite were mixed evenly, sprayed with water and stirred continuously, and then 6 parts of borax and 7 parts of silicate inorganic adhesive were added, stirred evenly and aged for 5 days;

[0035] (2) The aged material (water content 48%) is sent to a rotary kiln through a screw conveyor for drying and granulation, sintered at 1200° C. for 50 min, and finally cooled to room temperature by using a centrifugal fan to inhale cold air for heat exchange with the ceramsite.

[0036] Example 3

[0037] The method for preparing the high-strength porous ceramsite of this embodiment comprises the following steps:

[0038] (1) 40 parts of secondary aluminum ash, 35 parts of electroplating sludge, 6 parts of fly ash and 16 parts of bentonite were mixed evenly, sprayed with water and stirred continuously, and then 8 parts of calcium carbonate and 6 parts of silicate inorganic adhesive were added, stirred evenly and aged for 5 days;

[0039] (2) The aged material (water content 48%) is sent to a rotary kiln through a screw conveyor for drying and granulation, sintered at 1250° C. for 50 min, and finally cooled to room temperature by using a centrifugal fan to inhale cold air for heat exchange with the ceramsite.

[0040] Example 4

[0041] The difference between this embodiment and embodiment 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 15 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 6 parts of calcium carbonate and 6 parts of silicate inorganic adhesive are added, stirred evenly and aged for 2 days.

[0042] Example 5

[0043] The difference between this embodiment and embodiment 1 is that in step (2), the aged material (water content 48%) is sent to a rotary kiln by a screw conveyor for drying and granulation, sintered at 1000° C. for 50 min, and finally a centrifugal fan is used to inhale cold air for heat exchange with the ceramsite and cooled to room temperature.

[0044] Example 6

[0045] The difference between this embodiment and embodiment 1 is that in step (2), the aged material (water content 48%) is sent to a rotary kiln by a screw conveyor for drying and granulation, sintered at 1400° C. for 50 min, and finally a centrifugal fan is used to inhale cold air for heat exchange with the ceramsite and cooled to room temperature.

[0046] Comparative Example 1

[0047] The difference between this comparative example and Example 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 5 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 6 parts of calcium carbonate and 6 parts of silicate inorganic adhesive are added, stirred evenly and aged for 5 days.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 25 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 6 parts of calcium carbonate and 6 parts of silicate inorganic adhesive are added, stirred evenly and aged for 5 days.

[0050] Comparative Example 3

[0051] The difference between this comparative example and Example 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 15 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 3 parts of calcium carbonate and 6 parts of silicate inorganic adhesive are added, stirred evenly and aged for 5 days.

[0052] Comparative Example 4

[0053] The difference between this comparative example and Example 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 15 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 13 parts of calcium carbonate and 6 parts of silicate inorganic adhesive are added, stirred evenly and aged for 5 days.

[0054] Comparative Example 5

[0055] The difference between this comparative example and Example 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 15 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 6 parts of calcium carbonate and 3 parts of silicate inorganic adhesive are added, stirred evenly and aged for 5 days.

[0056] Comparative Example 6

[0057] The difference between this comparative example and Example 1 is that in step (1), 40 parts of secondary aluminum ash, 30 parts of electroplating sludge, 6 parts of fly ash and 15 parts of bentonite are mixed evenly, sprayed with water and stirred continuously, and then 6 parts of calcium carbonate and 13 parts of silicate inorganic adhesive are added, stirred evenly and aged for 5 days.

[0058] The performance of the high-strength porous ceramsite obtained in the above examples and comparative examples was tested, and the test results are shown in Table 1.

[0059] Table 1 High strength porous ceramsite performance data table

[0060]

[0061]

[0062] In Examples 1-3, secondary aluminum ash and electroplating sludge are used as main components, combined with fly ash, bentonite and other additives, and a rotary kiln is used for granulation, drying and high-temperature sintering to finally obtain porous ceramsite with high strength; in Example 4, the aging time is short, the uniformity of the raw materials is slightly poor, and the strength of the porous ceramsite obtained is low; in Example 5, the sintering temperature is too low, and it cannot be completely sintered, resulting in insufficient product strength; in Example 6, the sintering temperature is too high, resulting in excessive melting, affecting the pore structure and strength of the ceramsite; in Comparative Example 1, less bentonite is used, the reinforcing effect on the ceramsite is weakened, and the strength of the obtained ceramsite is reduced; in Comparative Example 2, more bentonite is used, the dispersion difficulty is increased, and the strength of the obtained ceramsite is slightly reduced; in Comparative Example 3, less calcium carbonate is used, the sintering efficiency is reduced, and the strength of the obtained ceramsite is reduced; in Comparative Example 4, more calcium carbonate is used, the porosity of the obtained ceramsite is increased, and the strength is reduced; in Comparative Example 5, less binder is used, the bonding effect is small, the molding stability is reduced, and the strength of the obtained ceramsite is slightly reduced; in Comparative Example 6, more binder is used, the bulk density of the obtained ceramsite is reduced, and the strength is reduced.

[0063] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A high-strength porous ceramsite, characterized in that: The invention comprises the following raw materials in parts by weight: 30 to 50 parts of secondary aluminum ash, 20 to 40 parts of electroplating sludge, 5 to 10 parts of fly ash, 10 to 20 parts of bentonite, 5 to 10 parts of flux and 5 to 10 parts of binder.

2. The high-strength porous ceramsite according to claim 1, characterized in that: The secondary aluminum ash is composed of the following components in weight percentage: 5-10% SiO2, 5-10% Al2O3, 1-5% Fe2O3, 1-5% CaO, 3-8% MgO, 0.10-0.40% Cu, 0.01-0.06% Ni, 0.05-0.20% Cr, 0.10-0.50% Zn, 0.03-0.08% Pb, and the balance is Al.

3. The high-strength porous ceramsite according to claim 1, characterized in that: The electroplating sludge is composed of the following components in weight percentage: 1-5% SiO2, 3-8% Al2O3, 8-15% Fe2O3, 20-28% CaO, 5-10% MgO, 0.05-0.20% Cu, 0.10-0.20% Ni, 0.15-0.25% Cr, 0.30-0.80% Zn, 0.01-0.03% Pb, and the balance is water.

4. The high-strength porous ceramsite according to claim 1, characterized in that: The flux is one or more of potassium carbonate, borax, anhydrous aluminum fluoride, magnesium fluoride, and calcium carbonate.

5. The high-strength porous ceramsite according to claim 1, characterized in that: The binder is one or more of a silicate binder, a phosphate binder, and an aluminate binder.

6. A method for preparing high-strength porous ceramsite as claimed in claim 1, characterized in that: The following steps are involved: (1) After the secondary aluminum ash, electroplating sludge, fly ash and bentonite are mixed evenly, water is sprayed and stirred continuously, and then flux and binder are added, stirred evenly and aged; (2) The aged material is sent to a rotary kiln through a screw conveyor for drying, granulation, sintering, and finally cooling.

7. The preparation method according to claim 6, characterized in that: The aging time in step (1) is 3 days or more.

8. The preparation method according to claim 6, characterized in that: The moisture content of the material obtained by aging in step (1) is 45% to 50%.

9. The preparation method according to claim 6, characterized in that: In step (2), the sintering temperature is 1100-1300° C. and the sintering time is 30-60 min.

10. The preparation method according to claim 6, characterized in that: In step (2), cooling is performed by using a centrifugal fan to suck in cold air to exchange heat with the ceramsite.

Citation Information

Patent Citations

  • Ceramsite foamed in situ by using secondary aluminum ash and preparation method thereof

    CN116606123A

Cited By

  • Preparation method and application of concrete filler based on secondary aluminum ash

    CN121225906A